ANÁLISE NOS ESCOLARES DE 4 E 5 ANOS DE IDADE: RECONHECIMENTO DAS CORES, MOTRICIDADE E COORDENAÇÃO FINA - Riva, Denise; Pretto, Luciana M.; Bonamigo, Elenita C. B.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo